Caregiver exposure to critical events and distress in home-based palliative care in Germany a cross-sectional study using the Stressful Caregiving Adult Reactions to Experiences of Dying (SCARED) scale - Michael Galatsch (BMC Palliative Care, 2019)
Abstract Background Lay family caregivers of patients receiving palliative care often confront stressful situations in the care of their loved ones. This is particularly true for families in the home-based palliative care settings, where the family caregivers are responsible for a substantial amount of the patient’s care. Yet, to our knowledge, no study to date has examined the family caregivers’ exposure to critical events and distress with home-based palliative care has been reported from Germany. Therefore, we attempt to assess family caregiver exposure to the dying patient’s critical health events and relate that to the caregiver’s own psychological distress to examine associations with general health within a home-based palliative care situation in Germany. Methods A cross-sectional study was conducted among 106 family caregivers with home-based palliative care in the Federal State of North Rhine Westphalia, Germany. We administered the Stressful Caregiving Adult Reactions to Experiences of Dying (SCARED) Scale. Descriptive statistics and linear regression models relating general health (SF-36) were used to analyze the data. Results The frequency of the caregiver’s exposure, or witness of, critical health events of the patient ranged from 95.2% “pain/discomfort” to 20.8% “family caregiver thought patient was dead”. The highest distress scores assessing fear and helpfulness were associated with “family caregiver felt patient had enough’” and “family caregiver thought patient was dead”. Linear regression analyses revealed significant inverse associations between SCARED critical health event exposure frequency (beta = .408, p = .025) and total score (beta = .377, p = .007) with general health in family caregivers. Conclusions Family caregivers with home-based palliative care in Germany frequently experience exposure to a large number of critical health events in caring for their family members who are terminally ill. These exposures are associated with the family caregiver’s degree of fear and helplessness and are associated with their worse general health. Thus the SCARED Scale, which is brief and easy to administer, appears able to identify these potentially upsetting critical health events among family caregivers of palliative care patients receiving care at home. Because it identified commonly encountered critical events in these patients and related them to adverse general health of family caregivers, the SCARED may add to clinically useful screens to identify family caregivers who may be struggling.